Circulating tumor cells in breast cancer: functional heterogeneity, pathogenetic and clinical aspects - Cherdyntseva, N.V.; Litviakov, N.V.; Denisov, E.V.; Gervas, P.A.; Cherdyntsev, E.S. (Experimental Oncology, 2017)
Each patient has a unique history of cancer ecosystem development, resulting in intratumor heterogeneity. In order to effectively kill the tumor cells by chemotherapy, dynamic monitoring of driver molecular alterations is necessary to detect the markers for acquired drug resistance and find the new therapeutic targets. To perform the therapeutic monitoring, frequent tumor biopsy is needed, but it is not always possible due to small tumor size or its regression during the therapy or tumor inaccessibility in advanced cancer patients. Liquid biopsy appears to be a promising approach to overcome this problem, providing the testing of circulating tumor cells (CTC) and/or tumor-specific circulating nucleic acids. Their genomic characteristics make it possible to assess the clonal dynamics of tumors, comparing it with the clinical course and identification of driver mutation that confer resistance to therapy. The main attention in this review is paid to CTC. The biological behavior of the tumor is determined by specific cancerpromoting molecular and genetic alterations of tumor cells, and by the peculiarities of their interactions with the microenvironment that can result in the presence of wide spectrum of circulating tumor clones with various properties and potentialities to contribute to tumor progression and response to chemotherapy and prognostic value. Indeed, data on prognostic or predictive value of CTC are rather contradictory, because there is still no standard method of CTC identification, represented by different populations manifesting various biological behavior as well as different potency to metastasis. Circulating clasters of CTC appear to have essentially greater ability to metastasize in comparison with single CTC, as well as strong association with worse prognosis and chemoresistance in breast cancer patients. The Food and Drug Administration (USA) has approved the CTC-based prognostic test for clinical application in patients with advanced breast cancer. Prospective clinical trials have demonstrated that measuring changes in CTC numbers during treatment is useful for monitoring therapy response in breast cancer patients. Molecular and genetic analysis of CTC gives the opportunity to have timely information on emergence of resistant tumor clones and may shed light on the new targets for pathogenetic antitumor therapy.